Long-Term and Transfer Effects of an Action Control Intervention in Overweight Couples: A Randomized Controlled Trial Using Text Messages - Berli, Corina; Scholz, Urte (Frontiers in Psychology, 2021)
Keeping a physically active lifestyle requires consistent self-regulatory effort such as action control (e.g., continuously monitoring and evaluating a behavior in terms of one’s goals). Involving the romantic partner in interventions might be particularly effective in the long run. The present study examined the long-term and transfer effects of an action control intervention in couples using text messaging for promoting target persons’ and partners’ physical activity, anthropometric measures and physical fitness six months post baseline. A total of 121 overweight and obese individuals and their romantic partnerscouples, randomly allocated to an intervention (n = 60; information + action control text messages) or a control group (n = 61; information only) and to participating as target person or partner, completed baseline assessments (T1). 100 couples (82.6%) completed the 6-months follow-up (T3) assessment. Primary outcomes included self-reported moderate-to-vigorous physical activity (MVPA) and objective MVPA and MVPA adherence using triaxial accelerometers across a diary period of 14 days after T3. Secondary outcomes included BMI, waist-to-hip circumference and physical fitness (target persons only) using a submaximal aerobic cycle test. At T3, there were no significant between-group differences between target persons’ and partner’s with regard to their objective MVPA, self-reported MVPA, BMI, waist-hip ratio or physical fitness. Overall, no significant changes in these outcomes were observed from T1 to T3; however, changes in BMI from T1 to T3 between target persons and partners in the intervention group were associated. Overall, the brief 14-days action control intervention was not effective in improving target person’s physical activity, body measures and physical fitness in the long-term. Moreover, no long-term benefits for partners emerged. While brief ecological momentary interventions text messages might be a promising tool for short-term effects, future studies are needed to test features enhancing long-term effectiveness. Associations in romantic partners’s changes suggest that dyadic interventions can be a promising approach, as changes induced in one partner may then transfer over to the other. (controlled-trials.com ISRCTN15705531)